Thermal Non-Equilibrium in Heterogeneous Media - de Lemos, Marcelo J.S (SpringerBriefs in Computational Mechanics, 2016)
This book presents, in a self-contained fashion, a series of studies on flow and heat transfer in porous media, in which distinct energy balances are considered for the porous matrix and for the permeating fluid. Detailed mathematical modeling is presented considering both volume and time averaging operators simultaneously applied to the governing equations. System involving combustion in the gaseous phase, moving bed and double-diffusion mechanism are analyzed. Numerical results are presented for each case. In the end, this book contains the description of a tool that might benefit engineers in developing and designing more efficient thermal equipment.